Axillary Metaplastic Breast Carcinoma with Ipsilateral Pectoral Invasive Ductal Carcinoma: An Unusual Presentation - Zhang, Lei (Hindawi Publishing Corporation, 2014)
We report a case of axillary metaplastic breast carcinoma (MBC) with triple negative (ER−/PR−/Her2−) phenotype, concurrent with multifocal invasive ductal carcinoma (IDC) of ipsilateral pectoral breast (ER+/PR+/Her2−) in a 60-year-old woman. The two tumors demonstrate different morphology, immunophenotype, and opposite response to neoadjuvant chemotherapy of paclitaxol, adriamycin, and cyclophosphamide. Methylation analysis of human androgen receptor (HUMARA) on X-chromosome identified monoclonal pattern of X-chromosome inactivation in MBC and mosaic pattern in the IDC. Stem cell origin of MBC is suggested in this case. Clinicopathological features, imaging findings, biological markers, chemoradiation management, and prognosis of MBC are reviewed in comparison to invasive ductal carcinoma. Our case and literature review suggest that traditional chemotherapy applicable to IDC is less effective towards MBC. However, new chemotherapy protocols targeting stem cell and multimodality management of MBC are promising. Recognition of unusual presentation of MBC will help tailor therapy towards tumor with worse prognosis.